Review of the Biomolecular Modification of the Metal-Organ-Framework - Xing, Qiqi; Pan, Yixiao; Hu, Yihe; Wang, Long (Frontiers in Chemistry, 2020)
Metal-organ frameworks (MOFs), as a kind of novel artificial material, have been widely studied in the field of chemistry. MOFs are capable of high loading capacities, controlled release, plasticity and biosafety because of their porous structure and have been gradually functionalized as a drug carrier. Recently, a completely new strategy of combining biomolecules, such as oligonucleotides, polypeptides and nucleic acids, with MOF nanoparticles was proposed. The synthetic bio-MOFs conferred strong protection and endowed the MOFs with particular biological functions. Biomolecular modification of MOFs to form bridges for communication between different subjects has received increased attention. This review will focus on bio-MOFs modification methods and discuss the advantages, applications, prospects and challenges of using MOFs in the field of biomolecule delivery.